Study of judicial legal person in appeal procedure from district court to provincial court in Thailand - Natchai Marpraneet (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
This research on the attitude of lawyers towards cases appealed from the District Court to the Provincial Court comes from a problem of the long-time adjudication timescale of cases in the Court of Appeal. This problem is inconsistent with the intention of establishing a District Court, aimed at adjudicating cases faster. This research employed a quantitative methodology in order to study the attitude of the lawyers, involved in the appeals to the District Court and on the appeal process of the Provincial Court. The sample group was 313 lawyers including judges, prosecutors, and attorneys. The instrument used in the study was a questionnaire. Descriptive and analytical statistics means, standard deviation, maximum and minimum scores, t-Test, and ANOVA were employed. The research found that the appeal of cases from the District Court to the Provincial Court was a fast track in judging the cases with a small amount of capital and a low rate of criminal penalties. This result is in accordance with the Classical Theory of Criminology focusing on the severity and certainty of legal punishment and the Theory of Deterrence explaining that an individual will consider the consequences of the law violation and restrain himself from crime. If the process of adjudication takes too long, this reflects the principle that justice delayed is justice denied. Moreover, the study showed that about 55.9% did not agree on the possibility of employing the appeals system of the Provincial Court instead of the Court of Appeal. Another 44.1% of the sample are unhappy with the current appeal system. The appeal system of the Provincial Court does not conflict with the concepts of neutrality, fairness, and the checks and balances because groups of judges in the District Court and the Provincial Court are separated from each other. Additionally, the seniority of the judges of the Provincial Court is equivalent that of the judges of the Court of Appeal before retirement. It also guarantees the right to due process as declared in Section 27 and 40 on adjudication in the Constitution of the Kingdom of Thailand, B.E. 2550. The researcher provided the following suggestions from the study: (1) to improve the appointment and tenure of provincial and district court judges based on their seniority; (2) to provide training or studying on the increasing potential of the judges in the Court of First Instance; and (3) to establish a pilot court or another appeal process for a clearer and better understanding of appealing cases from the District Court to the Provincial Court.